2018
DOI: 10.3847/2041-8213/aac2c5
|View full text |Cite
|
Sign up to set email alerts
|

Continued Brightening of the Afterglow of GW170817/GRB 170817A as Being Due to a Delayed Energy Injection

Abstract: The brightness of the multi-wavelength afterglow of GRB 170817A is increasing unexpectedly even ∼160 days after the associated gravitational burst. Here we suggest that the brightening can be caused by a late-time energy injection process. We use an empirical expression to mimic the evolution of the injection luminosity, which consists of a power-law rising phase and a power-law decreasing phase. It is found that the power-law indices of the two phases are 0.92 and −2.8, respectively, with the peak time of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…Indeed within the collapsar model (MacFadyen & Woosley 1999), as the jet gets through the collapsing progenitor star, the pressure of the surrounding gas collimates it (e.g., Zhang,Woosley & MacFadyen 2003;Morsony, Lazzati & Begelman 2007;Mizuta, Nagataki & Aoi 2011), thus the jet may have angular profiles of energy flux and Lorentz factor, namely a structured jet (e.g., Dai & Gou 2001;Rossi et al 2002;Zhang & Mészáros 2002;Zhang et al 2004;Beniamini & Nakar 2019). Noteworthily, this structured jet is well believed to exist in GRB 170817A (the first joint detection of short GRB and gravitational wave, Lazzati et al 2018;Lyman et al 2018;Meng et al 2018;Mooley et al 2018;Zhang et al 2018b;Ghirlanda et al 2019), whose unusual performance of the prompt emission and the afterglow has invoked hot debate (e.g., Ai et al 2018;Geng et al 2018b;Li et al 2018;Lin et al 2018;Geng et al 2019;Lan et al 2019;Li et al 2019;Wang et al 2019). Previously, Lundman et al (2013) showed that, with the collimated and steady-state jet the photospheric spectrum can reproduce the observed average low-energy photon index α ≈ −1.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed within the collapsar model (MacFadyen & Woosley 1999), as the jet gets through the collapsing progenitor star, the pressure of the surrounding gas collimates it (e.g., Zhang,Woosley & MacFadyen 2003;Morsony, Lazzati & Begelman 2007;Mizuta, Nagataki & Aoi 2011), thus the jet may have angular profiles of energy flux and Lorentz factor, namely a structured jet (e.g., Dai & Gou 2001;Rossi et al 2002;Zhang & Mészáros 2002;Zhang et al 2004;Beniamini & Nakar 2019). Noteworthily, this structured jet is well believed to exist in GRB 170817A (the first joint detection of short GRB and gravitational wave, Lazzati et al 2018;Lyman et al 2018;Meng et al 2018;Mooley et al 2018;Zhang et al 2018b;Ghirlanda et al 2019), whose unusual performance of the prompt emission and the afterglow has invoked hot debate (e.g., Ai et al 2018;Geng et al 2018b;Li et al 2018;Lin et al 2018;Geng et al 2019;Lan et al 2019;Li et al 2019;Wang et al 2019). Previously, Lundman et al (2013) showed that, with the collimated and steady-state jet the photospheric spectrum can reproduce the observed average low-energy photon index α ≈ −1.…”
Section: Introductionmentioning
confidence: 99%
“…After the successful detection of the first binary neutron star coalescence event (GW170817; )), a large number of follow-up observations have been carried out (e.g., Alexander et al 2017;Coulter et al 2017;Covino et al 2017;Cowperthwaite et al 2017;Goldstein et al 2017;Margutti et al 2017;Pian et al 2017;Savchenko et al 2017;Troja et al 2017), leading to a broad discussion on the physical picture underlying the multi-wavelength signals. In the field of short gammaray burst (sGRB), the energy flux of GRB 170817A, the observed inclination angle of the binary orbital axis with respect to our line of sight (although with a large uncertainty) as well as the behaviors of the X-ray and radio afterglow do help to constrain the GRB models Jin et al 2018;Lazzati et al 2018;Finstad et al 2018;Beniamini et al 2018;Yue et al 2018;Duan et al 2019); however, the central engine and how it powered the multi-wavelength emission is still in debate (Kasliwal et al 2017;Murguia-Berthier et al 2017;Yu et al 2018;Ma et al 2018;Meng et al 2018;Mooley et al 2018;Geng et al 2018;Lin et al 2018;Pooley et al 2018;Li et al 2018;Zhang et al 2018, see also Fan et al (2013) for a highly relevant investigation though on GRB 130603B, the first short event with a reliably identified macronova/kilonova signal that should have a neutron star merger origin too).…”
Section: Introductionmentioning
confidence: 99%
“…The slow but steady brightening was shown to be consistent with the presence of a jet, its energy contribution along the line of sight growing with the deceleration of the external shock (Xiao et al, 2017;De Colle et al, 2018;Finstad et al, 2018;Granot et al, 2018b;Lamb and Kobayashi, 2018;Lazzati et al, 2018;Fraija et al, 2019a;Fraija et al, 2019b;Beniamini et al, 2020b;Oganesyan et al, 2020). However, a radially stratified spherical outflow could reproduce the observations as well, albeit at the price of adding a never observed before component to the models (Li et al, 2018;Mooley et al, 2018c;Nakar and Piran, 2018;Salafia et al, 2018). Some evidence in favor of a jet was provided by the steep post-peak decay at all wavelengths (Alexander et al, 2018;Jin et al, 2018;Mooley et al, 2018b;Nynka et al, 2018;Fong et al, 2019;Hajela et al, 2019).…”
Section: The Afterglowmentioning
confidence: 84%